Associated Risk Factors during 24th to 28th Week Gestational Age among Pregnant Women Attending a Tertiary Care Hospital (Bangladesh Journal of Medical Biochemistry, 2025)
GDM is one of the most common non-communicable diseases globally. Gestational diabetes mellitus (GDM) is a heterogenous group of metabolic disorders, which result in varying degrees of maternal hyperglycemia and pregnancy associated risk. GDM is known to vary widely depending on the region of country, dietary habits, socioeconomic status, parity, family history of diabetes, hypertension and past history of GDM. This study was carried out in the department of biochemistry of BIRDEM general hospital, Dhaka from July 2014 to June 2015 to find out the risk factors of the women attending antenatal care (ANC) clinic at BIRDEM general hospital, Dhaka. This study enrolled pregnant women, with their estimated gestational age between 24th to 28th weeks, attending antenatal care (ANC) clinic at BIRDEM general hospital. A proforma containing general information on demographic characteristics, socio-economic status, parity, family history of diabetes, hypertension and past history of GDM was filled in. A total of 135 women participated in the study and GDM was diagnosed in 41 (30.37%) women and 94 (69.63%) were non-GDM subjects. Risk factors found to be significantly associated with GDM were family history of diabetes, age, educational level, BMI, past history of GDM. In this study, it was observed that highest frequency of GDM was in the age group of more than 30 years. Thirty one (75.6%) patients had family history of DM. So GDM patients had significantly positive family history. Twenty six (63.4%) multigravida mothers were more prone to develop GDM than primigravida pregnant mothers.Bangladesh J Med Biochem 2020; 13(2): 40-46